2000
DOI: 10.1046/j.1570-7458.2000.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition experience on a host‐infested plant affects flight and antennal searching behavior of Cotesia kariyai toward the host‐plant complex

Abstract: The flight response of Cotesia kariyai Watanabe (Hymenoptera: Braconidae), a parasitoid of the polyphagous herbivore, Mythimna separata Walker (Lepidoptera: Noctuidae), to pairs of different plant species infested by M. separata larvae was tested under a dual choice condition in the laboratory. The oviposition‐inexperienced (naive) wasps showed preference in the order: corn > kidney bean > Japanese radish. Wasps that had previously oviposited on the less preferred plant in a pair were found to have shifted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Kester & Barbosa 1991;Petitt et al 1992;Dutton et al 2000;Fujiwara et al 2000). Our experiments on exposure of parasitoids at different developmental stages to olfactory cues demonstrate that it is from the egg to the early larval stage in which learning occurs, leading to a strong adult response to host frass.…”
Section: Discussionmentioning
confidence: 73%
“…Kester & Barbosa 1991;Petitt et al 1992;Dutton et al 2000;Fujiwara et al 2000). Our experiments on exposure of parasitoids at different developmental stages to olfactory cues demonstrate that it is from the egg to the early larval stage in which learning occurs, leading to a strong adult response to host frass.…”
Section: Discussionmentioning
confidence: 73%
“…Several Cotesia species can innately respond to the host-infested plant volatiles and learn to associate the induced volatiles with a host (Cotesia marginiventris, Turlings et al, 1993;Cotesia glomerata, Geervliet et al, 1998). Fujiwara et al (2000b) previously reported that C. kariyai changed their innate preference between two blends of volatiles emitted from different plant species infested with the host larvae through preference learning. However, detailed understanding of the ability for learning this wasp remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…This acquired feeding inhibition implies that in a patch containing superior sugars such as glucose, sucrose or fructose, parasitoids rapidly give up the lesser quality food in favor of foraging for the nutritionally superior sugars. Similarly, parasitoids effectively discriminate between hosts in and among patches containing different qualities of hosts, and they change host acceptance based on previous experience (Papaj and Vet, 1990;Poolman Simons et al, 1992;Geervliet et al, 1998;Duan and Messing, 1999;Fujiwara et al, 2000). Surprisingly, also in the case of fructose we see a pronounced reduction in feeding time following exposure to glucose or sucrose; this phenomenon was consistently observed in multiple experiments and with both colonies of M. croceipes.…”
Section: Gustatory Discrimination Between Sugarsmentioning
confidence: 52%